Investigations of Vestnik-1 Site in 2021–2023 - Chistov, Dmitry (Hyperboreus, 2024)
In 2021, the Hermitage organized a new East Bosporan expedition whose main task was to study ancient sites from the Asian part of the Bosporan Kingdom. The first object of research of the Hermitage mission was the rural site Vestnik-1, located near the village of Vestnik in the vicinity of Anapa. During three field seasons on the site, the immediate surroundings of the monumental Greek public building discovered earlier were investigated. A late annex to it, dating back to the first half of the 4th century BC, was uncovered. Three funerary structures were discovered on the necropolis, probably serving as collective family tombs. The investigated burials belong to the indigenous Sindian population and date from the third quarter of the 6th to the second quarter of the 5th century BC.